2014
DOI: 10.2337/db14-1166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Impaired Glucose Tolerance on Organ-Specific Dietary Fatty Acid Metabolism in Humans

Abstract: Oral 14(R,S)-[18 F]-fluoro-6-thia-heptadecanoic acid was used to determine whether an increase in cardiac dietary fatty acid (DFA) metabolism in impaired glucose tolerance (IGT) is different in men and women. Myocardial DFA partitioning after 6 h was higher in IGT versus control subjects (P = 0.006) in both men (2.14 [95% CI sex difference. Men had higher net myocardial DFA uptake between time 90 and 120 min driven by higher chylomicrontriglyceride (TG) levels. IGT-associated increased cardiac DFA partitioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…We previously found that subjects with IGT display an increase in myocardial DFA uptake that is associated with decreased left ventricular function (14,22), an abnormality that was corrected by modest weight loss after a 1-year individually tailored lifestyle intervention (15). Here, we found that the improvement of insulin resistance with a 7-day hypocaloric, low-SFA diet did not change early 2-h postprandial myocardial DFA uptake in subjects with IGT.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We previously found that subjects with IGT display an increase in myocardial DFA uptake that is associated with decreased left ventricular function (14,22), an abnormality that was corrected by modest weight loss after a 1-year individually tailored lifestyle intervention (15). Here, we found that the improvement of insulin resistance with a 7-day hypocaloric, low-SFA diet did not change early 2-h postprandial myocardial DFA uptake in subjects with IGT.…”
Section: Discussionmentioning
confidence: 51%
“…Despite the small number of participants, the a priori power of our study for most outcomes ranged between 70% and 95%. The small number of men and women limits our power to detect sex differences in the contribution of adipose tissues versus direct chylomicron-TG uptake to cardiac DFA partitioning (22). Another limitation of our study is that the PET ventriculography method may not be as sensitive as cardiac MRI or echocardiography to detect changes in left ventricular diastolic function.…”
Section: Discussionmentioning
confidence: 94%
“…10 The small number of women is also a limitation given that sex is an important determinant of VLDL metabolism in healthy subjects. 3 In addition, there is a marked sexual dichotomy in cardiac and adipose tissue-specific chylomicron fatty acid uptake in subjects with impaired glucose tolerance, 18 suggesting that sex may influence…”
Section: See Accompanying Article On Page 2218mentioning
confidence: 99%
“…The selection criteria and absence of healthy controls may, however, have favored a stronger correlation between apoCIII levels and VLDL 1 kinetics compared with other lipoproteins, such as apolipoprotein E given that apoCIII-rich VLDL secretion is increased in hypertriglyceridemic individuals. 10 The small number of women is also a limitation given that sex is an important determinant of VLDL metabolism in healthy subjects.3 In addition, there is a marked sexual dichotomy in cardiac and adipose tissue-specific chylomicron fatty acid uptake in subjects with impaired glucose tolerance, 18 suggesting that sex may influence More mechanistic studies are clearly needed on these important sex-related differences in triglyceride metabolism. The study by Borén et al contributes to the remarkable and rapid recent advances in our understanding of the factors leading to hypertriglyceridemia associated with abdominal obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation